2021
DOI: 10.3390/sym13112220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Light Stress on the Synthesis of Both Antioxidants Polyphenols and Carotenoids, as Fast Photoprotective Response in Chlamydomonas reinhardtii: New Prospective for Biotechnological Potential of This Microalga

Abstract: The aim of this study was to investigate the potential role of the microalga Chlamydomonas reinhardtii as an antioxidant source of enriched biomass. This microalga is a model organism deeply investigated for physiological studies, particularly considering carotenoid synthesis in response to stress, to counteract the effects of the formation of free radicals. Less attention has been paid to the profile characterization of other antioxidant compounds, such as polyphenols, which can be synthesized, concomitantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(60 reference statements)
0
1
0
1
Order By: Relevance
“…Moreover, the existing literature lacks a thorough elucidation of the phenolic composition specific to this particular genus of microalga. Among the few available studies, in a recent one by Faraloni et al [43], the green microalga Chlamydomonas reinhartii showed lower levels of phenolic compounds, especially of chlorogenic, coumaric, and gallic acid, compared to those we found in ChA. Goiris et al [57] studied simple phenols and flavonoids in different microalgal biomass samples and detected p-coumaric, ferulic, and caffeic acid, quercetin, phloretin, apigenin, kaempferol, and catechin but to a lesser extent.…”
Section: Phenolic Compounds Profiling By Uhplc-esi-ms/msmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the existing literature lacks a thorough elucidation of the phenolic composition specific to this particular genus of microalga. Among the few available studies, in a recent one by Faraloni et al [43], the green microalga Chlamydomonas reinhartii showed lower levels of phenolic compounds, especially of chlorogenic, coumaric, and gallic acid, compared to those we found in ChA. Goiris et al [57] studied simple phenols and flavonoids in different microalgal biomass samples and detected p-coumaric, ferulic, and caffeic acid, quercetin, phloretin, apigenin, kaempferol, and catechin but to a lesser extent.…”
Section: Phenolic Compounds Profiling By Uhplc-esi-ms/msmentioning
confidence: 65%
“…[41,42]. It is interesting to note that in a recent study by Faraloni et al [43], Chlamydomonas reinhardtii, a green alga of the same genus of ChA, exhibited an enhanced production of polyphenols when exposed to high levels of light, thus indicating that light exposure levels also can influence total phenols content. The polyphenolic content of our extract from ChA was similar to those obtained by Goiris et al [41], who examined biomass from 32 microalgal species and reported an average total polyphenol content of 211 mg GAE/100 g dw.…”
Section: Bioactive Compounds Quantitation and Antioxidant Activity Of...mentioning
confidence: 91%
“…Nevertheless, considering that treatments with higher levels of phenols are also less productive, it is probable that both the control plants and the Cu-treated plants have bolstered secondary metabolic pathways at the expense of primary ones ( Prinsloo and Nogemane, 2018 ; Ciriello et al., 2022b ). Phenolic compounds have an antioxidant activity higher than vitamins since they can prevent ROS formation and improve antioxidant cell response due to their ability to chelate metal ions ( Faraloni et al., 2021 ). The problem of excess light correlated to high polyphenols content was not present in the other plant treatments, which showed higher transpiration and carboxylation activity, but significantly lower polyphenols, except for Cu treatment, even if at a lower extent, but without negative consequences on plant fresh weight.…”
Section: Discussionmentioning
confidence: 99%
“…produced higher concentrations of phenolic compounds during stress. The green alga, Chlamydomonas reinhardtii, was able to increase the production of polyphenols during a high light exposure [33]. Anwer et al (2022) determined the total phenol content from several microalgal species using different types of extraction.…”
Section: Phenolic Compoundsmentioning
confidence: 99%